Resilience in Latin America : Lessons from Macroeconomic Management and Financial Policies - De Gregorio, Jose (IMF Working Papers; Working Paper ;, 2013)
This paper analyzes the unprecedented resilience of Latin American countries to the global financial crisis. It argues that sound macroeconomic conditions, which allowed an unusual monetary and fiscal expansion, exchange rate flexibility, a strong and well--regulated financial system, high level of reserves, and a bit of luck coming from very high terms of trade, were central to good economic performance. Persevering along the road of strong macroeconomic and financial policies is necessary, but not sufficient, to go from recovery to sustained growth.